PAJAK MELINDUNGI KETERSEDIAAN AIR TANAH TAX PROTECTING GROUND WATER AVAILABILITY - Sunarti, Eka Sri (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2011)
Republic of Indonesia as a unitary State adheres to the principle of decentralization ingovernance, by providing the opportunity and flexibility to the regions to holdregional autonomy. To support the implementation of regional autonomy is set anddetermined the financial resources of the Region, including Regional Tax regulatedby Law Number 28 of 2009 on Local Taxes and Levies. Along with population andindustrial growth, demand for clean water needs increased rapidly. Related to theuse of surface water has been siphoned off and making excessive undergroundwater, it caused the surface soil decreases. How State and Local Governmentauthority to manage ground water and how should the Local Rules governing themanagement of ground water tax in the future. In the context of mastery of WaterResources in the territory of Indonesia, the mastery is right there in the country.Countries in this Region Government shall be responsible for the problems orenvironmental problems, ecological or any matters relating to public policy onenvironmental issues and natural resources. Tax on water can be imposed on provincialtaxes or tax district of the city. With the taxation of ground water to the society thenthe pattern of use of ground water will be limited. Taxation functions of groundwater that is to be made patterns and taxation systems that can regulate groundwater usage patterns and utilization of underground water so that soil water availabilitycan be maintained.